Influence of sublethal exposure to triflumuron on the biological performance of Tetranychus urticae Koch (Acari: Tetranychidae) - Saenz de Cabezon, F.J.=700 1 Martinez Villar, E.; Moreno, F.; Marco, V.; Perez Moreno, I.
(Es, En)
ilus., 23 ref.
Keywords: TETRANYCHUS URTICAE; CONTROL DE PLAGAS; PRODUCTOS QUIMICOS AGRICOLAS; TASA DE MORTALIDAD; ESPAÑA; ARAÑA AMARILLA; BENZOILFENIL UREAS; COEFICIENTE DE INCREMENTO INTRINSECO